2016
DOI: 10.1021/acsbiomaterials.6b00196
|View full text |Cite
|
Sign up to set email alerts
|

3D-Bioprinting of Polylactic Acid (PLA) Nanofiber–Alginate Hydrogel Bioink Containing Human Adipose-Derived Stem Cells

Abstract: Bioinks play a central role in 3D-bioprinting by providing the supporting environment within which encapsulated cells can endure the stresses encountered during the digitally driven fabrication process and continue to mature, proliferate, and eventually form extracellular matrix (ECM). In order to be most effective, it is important that bioprinted constructs recapitulate the native tissue milieu as closely as possible. As such, musculoskeletal soft tissue constructs can benefit from bioinks that mimic their na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(173 citation statements)
references
References 93 publications
3
166
0
4
Order By: Relevance
“…Improved mechanical properties and biological properties Cartilage [91] Fiber 3D plotting Acrylamide Cellulose short fibril Anisotropic swelling behaviors 4D printing [92] 3D plotting Alginate PLA continuous nanofiber Improved mechanical properties and biological properties Cartilage [93] Casting + 3D plotting PEGDGE, Acrylamide PU continuous microfiber Improved mechanical properties General [94] 3D plotting Alginate, Acrylamide Emax (UV-curable epoxy)…”
Section: Improved Radiopacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Improved mechanical properties and biological properties Cartilage [91] Fiber 3D plotting Acrylamide Cellulose short fibril Anisotropic swelling behaviors 4D printing [92] 3D plotting Alginate PLA continuous nanofiber Improved mechanical properties and biological properties Cartilage [93] Casting + 3D plotting PEGDGE, Acrylamide PU continuous microfiber Improved mechanical properties General [94] 3D plotting Alginate, Acrylamide Emax (UV-curable epoxy)…”
Section: Improved Radiopacitymentioning
confidence: 99%
“…Fiber reinforcements can also improve mechanical properties of hydrogel matrix in which the fiber contents and its distribution inside its matrix determine mechanical properties such as stiffness and strength of composites [92][93][94][95] . In the case of common 3D printing systems, short fiber reinforcements are the most commonly used due to its easy processing procedure at low cost.…”
Section: Fiber-reinforced Hydrogel Composites 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, various designed 3D print structures are easily obtained through combining 3D printing technique with imaging or graphics techniques . Recently, 3D‐printed NFHGs with designed tissue constructs were successfully prepared by taking mixtures of alginate hydrogel, PLA nanofibers, and stem cells as fibrous bioink ( Figure ) . Conventionally, printable ink with appropriate viscosity and shear‐thinning properties is the most vital part of the 3D printing technique, because of the significant influences on the formability of printed 3D materials.…”
Section: Strategies To Synthesize Nfhgsmentioning
confidence: 99%
“…In attempt to combat the cellular viability dilemma, Narayanan et al . recently demonstrated that by blending a PLA nanofibrous matrix with alginate hydrogel, cellular viability could further be enhanced through ECM mimicry . Human adipose‐derived stem cells were cultured in vitro over an 8‐week period after bioprinting with and without the nanofibrous matrix blend.…”
Section: Printing Proceduresmentioning
confidence: 99%